2010
DOI: 10.5012/bkcs.2010.31.11.3327
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Lowering and Antioxidant Effects of Newly Synthesized 4-[(Butylsulfinyl)methyl]-1,2-benzenediol (SMBD) in Diet-induced Hypercholesterolemic Rabbits

Abstract: We investigated the effects of newly synthesized 4-[(butylsulfinyl)methyl]-1,2-benzenediol (SMBD) on the prevention of atherosclerosis in hypercholesterolemic rabbits. SMBD exhibited stronger inhibition of Cu 2+ -induced low-density lipoprotein oxidation than that of ascorbic acid or simvastatin. Three-month-old rabbits were fed an atherogenic diet containing 0.5% cholesterol and 10% coconut oil, while other two groups were given an atherogenic diet with intravenous injection of either simvastatin or SMBD (0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, the dimethyl sulfoxide (DMSO), with two alkyl groups, has been reported to be an effective scavenger of reactive oxygen radicals [22,23,24]. Recently, Kim et al [25] chemically synthesized 4-[(butylsulfinyl)methyl]-1,2-benzenediol (SMBD, Figure 1A) with a combination of catechol and DMSO, and found that SMBD shows antioxidant effects by lowering plasma lipid levels and decreasing aortic thickness, ROS generation and COX-2 protein expression in cholesterol diet-induced hypercholesterolemic rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the dimethyl sulfoxide (DMSO), with two alkyl groups, has been reported to be an effective scavenger of reactive oxygen radicals [22,23,24]. Recently, Kim et al [25] chemically synthesized 4-[(butylsulfinyl)methyl]-1,2-benzenediol (SMBD, Figure 1A) with a combination of catechol and DMSO, and found that SMBD shows antioxidant effects by lowering plasma lipid levels and decreasing aortic thickness, ROS generation and COX-2 protein expression in cholesterol diet-induced hypercholesterolemic rabbits.…”
Section: Introductionmentioning
confidence: 99%